Ocular Sarcoidosis Limited to Retinal Vascular Ischemia and Neovascularization - Dyer, Gawain (Cureus, 2016)
A 59-year-old Caucasian male experienced progressive vision loss secondary to retinal vascular ischemia and neovascularization. At no time did he present with uveitis or vasculitis, and his serology tests were all negative. He was soon after diagnosed with sarcoidosis by hilar lymph node lung biopsy. Our patient demonstrates an atypical presentation of ocular sarcoidosis, manifesting solely as neovascularization and retinal vascular ischemia. Ophthalmologists should consider proliferative sarcoid retinopathy in patients with neovascularization.